2020
DOI: 10.5339/qmj.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of a salmonella outbreak among infants in Qatar, 2017

Abstract: Purpose: This study was conducted to investigate the epidemiology behind the increased incidence of infant salmonella cases in Qatar during 2017 and identify the possible risk factors. Methods: This was a cross-sectional study using the notification reports of laboratory-confirmed infant salmonella cases received by the Ministry of Public Health during the year 2017. Furthermore, complementary phone interviews with the infants’ mothers using a validated questionnaire were conducted. Results: The infant salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…The Salmonella spp. rate of 12 (7.5%) found in this study is higher than the rates found in other studies, including those from retail meat and meat products in China at 3.6% [25], Ethiopia at 6.9% [26], Ethiopia at 1% [5], India at 1% [27] and Qatar at 3.23% [28]. Meanwhile, the Salmonella spp.…”
Section: Discussioncontrasting
confidence: 73%
“…The Salmonella spp. rate of 12 (7.5%) found in this study is higher than the rates found in other studies, including those from retail meat and meat products in China at 3.6% [25], Ethiopia at 6.9% [26], Ethiopia at 1% [5], India at 1% [27] and Qatar at 3.23% [28]. Meanwhile, the Salmonella spp.…”
Section: Discussioncontrasting
confidence: 73%